Pengaruh Social Media Promotion, Menu Variation dan Price Bundling Terhadap Purchasing Decisions Home service Mau Grill - Riansyah, Priyadana Sura; Farida, Eka; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2024)
Abstract UMKM play an important role in the Indonesian economy. UMKM are the backbone of the Indonesian economy which makes a significant contribution to economic growth, job creation and income distribution for Indonesian society. This research aims to determine the Influence of Social Media Promotion, Menu Variation and Price Bundling on Purchasing Decisions for Home service Mau Grill. This research uses quantitative methods. The respondents of this research were 91 Mau Grill consumers. Data collection uses a questionnaire with a scale of 1 to 5. The results of this research explain that 1) Simultaneously, the variables of social media promotion, menu variation, and price bundling have a positive and significant effect on the purchasing decisions of Mau Grill products. 2) Social Media Promotion has a positive and significant effect on purchasing decisions for Mau Grill products. 3) Menu Variation has a positive and significant effect on purchasing decisions for Mau Grill products. 4) Price Bundling has an effect positive and significant on purchasing decisions for Mau Grill products Keywords: Social Media Promotion, Menu Variation, Price Bundling, Purchasing Decisions